Bilateral Relations Between Indonesia-Japan in Improving the Quality of Education in Indonesia - Fathun, Laode Muhamad; Nidatya, Nurfarah; Nathania, Vania Zahra; Nurshadrina, Dilla Andieni; Wahidah, Tuhfahtu Hasanatul (Sekretariat Jenderal DPR RI, 2025)
This study aims to explain the contributions of state and non-state actors in improving the quality of education in Indonesia, focusing on Japan as the state actor and The Japan Foundation as the non-state actor. Previous studies have mainly emphasized the economic and political aspects of Indonesia–Japan relations, while the educational dimension has received relatively less attention. Therefore, this study addresses that gap by analyzing education as an instrument of soft power and institutional coordination in bilateral relations. A mixed-methods approach was employed, combining a survey of 100 International Relations students, interviews, and literature review. The analysis is grounded in Nye’s soft power theory and institutional coordination framework. The findings reveal that Japan’s contribution to Indonesia’s education sector is realized through educational, financial, and technological assistance, as well as scholarship programs. Meanwhile, The Japan Foundation fosters a cultural and learning ecosystem through language courses, exchange programs, and the promotion of popular culture. These findings emphasize that the collaboration between state and non-state actors not only strengthens the quality of education in Indonesia but also represents an effective model of educational diplomacy in international relations. The academic contribution of this study lies in emphasizing education as a strategic soft power instrument to deepen bilateral relations and build long-term strategic trust.